Variation in subnational electoral authoritarianism: evidence from the Russian Federation. Issue 3 (15th April 2016) - Saikkonen, Inga A.-L.
Abstract : Despite the burgeoning comparative literature on electoral authoritarian regimes, fewer studies have accounted for the emergence of hegemonic and competitive authoritarian regimes at the subnational level. This article examines the variation in subnational electoral authoritarianism with data from the Russian Federation. First, the article shows that by using a comparative regime classification most Russian subnational cases can be classified as electoral authoritarian between 1991 and 2005. Yet, there are considerable differences in competitiveness between the electoral authoritarian regimes. The article accounts for this variation by drawing on both comparative electoral authoritarianism literature as well as more context-specific explanations. Statistical analysis on 192 subnational electoral authoritarian cases shows that the determinants of Russian subnational authoritarian stability are rather similar to those found in cross-national studies. Subnational (non)competitiveness in Russia appears to be related to the structure of the regional economy and natural resource rents, and to a lesser degree to the specific Russian federal context. Authoritarian "know how" also plays a role in authoritarian regime building. The findings of the article contribute to the literature on electoral authoritarianism, subnational democratization and Russian subnational politics.